2022
DOI: 10.3390/nu14020339
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Phone Radiation Deflects Brain Energy Homeostasis and Prompts Human Food Ingestion

Abstract: Obesity and mobile phone usage have simultaneously spread worldwide. Radio frequency-modulated electromagnetic fields (RF-EMFs) emitted by mobile phones are largely absorbed by the head of the user, influence cerebral glucose metabolism, and modulate neuronal excitability. Body weight adjustment, in turn, is one of the main brain functions as food intake behavior and appetite perception underlie hypothalamic regulation. Against this background, we questioned if mobile phone radiation and food intake may be rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…Among that, the role of Beclin1 in miR-30a-regulated autophagy has been widely studied [ 33–36 ]. In our research and from other scholars, microwave radiation can induce abnormal energy metabolism in neurons [ 20 , 21 , 37 , 38 ]. Studies have confirmed that microwave under certain conditions can promote the occurrence of autophagy, but the underlying mechanisms have yet to be clarified [ 12 , 39–42 ].…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Among that, the role of Beclin1 in miR-30a-regulated autophagy has been widely studied [ 33–36 ]. In our research and from other scholars, microwave radiation can induce abnormal energy metabolism in neurons [ 20 , 21 , 37 , 38 ]. Studies have confirmed that microwave under certain conditions can promote the occurrence of autophagy, but the underlying mechanisms have yet to be clarified [ 12 , 39–42 ].…”
Section: Resultssupporting
confidence: 56%
“…Through bioinformatics analysis, we predicted the target genes of miR-30a that might be involved in autophagy regulation, including Beclin1, Prkaa2, Irs1, Pik3r2, Rras2, Ddit4, Gabarapl2 and Atg12. Studies have demonstrated that microwave radiation leads to abnormal energy metabolism in neurons [ 20 , 21 , 37 , 38 ]. In the present study, we showed that microwave radiation activated AMPK signal, a cellular energy sensor, both in rat hippocampi and neuron-like cells.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the extent of the health risk posed by RF radiation is still necessary. Numerous research examine the effects of mobile phones [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…We are somewhat surprised about the extent of the feedback that we received upon our publication [ 1 ], in terms of the not entirely new connection between mobile phone radiation, brain activity, and food intake, being previously explored by EEG, association studies, and animal experiments (as outlined in the introduction of our paper). Ten years ago, scientists found “alarming” evidence of a long-term association between mobile phone radiation and obesity in humans [ 2 ].…”
mentioning
confidence: 99%